The Naqshbandi Order and the Internalization of Sharia Values: A Maqāṣid al-Sharī'ah Framework in Secular Turkey - Syaifuddin, Helmi; Prastyo, Angga Teguh; Baharuddin, Baharuddin; Bakar, Abu; Ghaffar, Abdul; Khasani, Fahim; Gundogdu, Yusuf Bahri (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines the internalization of Sharia values within secular Turkish society through the maqāṣid al-sharī'ah framework. It focuses specifically on the Naqshbandi Sufi order, one of the most influential Sufi movements in contemporary Turkey. The research is based on qualitative data collected from 12 participants, consisting of Naqshbandi sheikhs, senior disciples, community educators, and active members in Istanbul, Ankara, and Konya. Data were gathered through in-depth interviews, direct observation of dhikr assemblies and community activities, documentary analysis, and review of academic literature and podcasts related to Sufism and Sharia. Content analysis was conducted using four analytic categories: leadership charisma, institutional networks, pedagogical practices, and community-based religious activities. Data validity was strengthened through triangulation across interviews, observations, and documentary sources. The findings reveal that although the Naqshbandi order maintains a strong ethical and spiritual foundation, deeper internalization of Sharia values still requires sustained cross-community dialogue, institutional capacity building, and the development of interpretive frameworks that bridge classical Islamic traditions and modern scholarly frameworks. The study concludes that cultivating sharī‘ah values in a secular national context requires balancing respect for tradition with adaptation to contemporary social challenges, thereby fostering ethical, contextually relevant, contextually relevant, and sustainable forms of spiritual and social practice.